Three-Pronged Approach to Curb Cancer Metastasis - Jariya Kalsoom; Sadaf Naeem (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Extracellular signal-regulated kinases 1 and 2 [ERK1/2] have been reported to promote cancer spread through receptor tyrosine kinase (RTK)/Ras/Raf/MEK/ERK1/2 pathway hyperactivation. The extracellular signal-regulated kinase ERK5 has also been linked to cancer. However, inhibition of ERK1/2 has been reported to cause compensatory hyperactivation of the ERK5 pathway. Therefore, there is a need for simultaneous inhibition of this trio by a common inhibitor. This study aimed to find a novel common inhibitor for ERK1, ERK2 and ERK5, with a special focus on phytochemicals. METHODOLOGY: All the available co-crystallized inhibitors of MEK1, ERK1/2 and ERK5 were used as references for 2D search across zillions of compounds. One hundred molecules with the best matching pharmacophores were extracted per virtual chemical space. A total of 20,000 new structurally diverse chemical entities with scaffold hopping ability were sifted out from these chemical spaces. Virtual screening of ERK1/2 and ERK5 was performed against these compounds. The successfully docked molecules with estimated affinities less than 500 nm were filtered. These filtered protein-molecule complexes of ERK1/2 and ERK5 were exported as Excel sheets, which were then compared to find any overlapping inhibitors. Four novel common/overlapping potential inhibitors were identified. Their pose views were generated, and binding interactions were analyzed. These novel compounds were compared for their absorption, distribution, metabolism, excretion and toxicity (ADME-Tox) properties. RESULTS: The molecules m240690bcc215667167368734, rxn109fEMOL37110279EMOL314046334 and LIND027BT1904LN00213276AK0086 showed good binding affinities to the conventional ATP binding pockets of the kinases ERK1/2 and ERK5. CONCLUSION: These novel compounds may be proposed as potential common inhibitors of ERK1, 2 and 5. Further in silico analysis and in vitro testing of proteins are required to confirm their inhibitory potential.